Wspólnotowość (w) edukacji. Problem demokratycznego współistnienia - Segiet, Waldemar (Pedagogika Społeczna Nova, 2021)
What I associate with the title of this article is the potential of discussions on education, which is also confirmed by attempts to combine themes selected from within it with those concerning community. I propose a precise study, which includes many pointers, and also doubts, concerning the role of edu- cation itself, mainly in the implementation of social cohesion and activities for fostering the integration of those involved in it. A specific feature of these reflections on the need to achieve community, and to confirm it in and through education, is the encouragement to engage in issues related to social (dis) integration, which is intentionally filled with aspects directly related to democracy itself.